Butyrate: Connecting the gut-lung axis to the management of pulmonary disorders - Corrêa, Renan Oliveira; Castro, Pollyana Ribeiro; Moser, René; Ferreira, Caroline Marcantonio; Quesniaux, Valerie F. J.; Vinolo, Marco Aurélio Ramirez; Ryffel, Bernhard (Frontiers in Nutrition, 2022)
Short-chain fatty acids (SCFAs) are metabolites released by bacterial components of the microbiota. These molecules have a wide range of effects in the microbiota itself, but also in host cells in which they are known for contributing to the regulation of cell metabolism, barrier function, and immunological responses. Recent studies indicate that these molecules are important players in the gut-lung axis and highlight the possibility of using strategies that alter their intestinal production to prevent or treat distinct lung inflammatory diseases. Here, we review the effects of the SCFA butyrate and its derivatives in vitro and in vivo on murine models of respiratory disorders, besides discussing the potential therapeutic use of butyrate and the other SCFAs in lung diseases.